2022
DOI: 10.1111/jce.15470
|View full text |Cite
|
Sign up to set email alerts
|

Novel “late potential map” algorithm: Abnormal potentials and scar channels detection for ventricular tachycardia ablation

Abstract: Background: Automated systems for substrate mapping in the context of ventricular tachycardia (VT) ablation may annotate far-field rather than near-field signals, rendering the resulting maps hard to interpret. Additionally, quantitative assessment of local conduction velocity (LCV) remains an unmet need in clinical practice. We evaluate whether a new late potential map (LPM) algorithm can provide an automatic and reliable annotation and localized bipolar voltage measurement of ventricular electrograms (EGMs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The identification of the ISCC was purely based on the analysis of LCV vectors, using simple criteria recently proposed by our group. 12 Additionally, we used for the first time a novel propagation display of the LCV data superimposed on the activation maps, as shown in Supplementary Movie 1, which made the delineation of ISCC much easier. In the current study, we found that 66% of ISCCs were similarly identified in all available activating wavefronts per patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of the ISCC was purely based on the analysis of LCV vectors, using simple criteria recently proposed by our group. 12 Additionally, we used for the first time a novel propagation display of the LCV data superimposed on the activation maps, as shown in Supplementary Movie 1, which made the delineation of ISCC much easier. In the current study, we found that 66% of ISCCs were similarly identified in all available activating wavefronts per patient.…”
Section: Discussionmentioning
confidence: 99%
“…Maps were analyzed retrospectively using a noncommercial version of Carto®3 V8. The substrate map was analyzed using a new late potential map (LPM) software, which includes: a LAVA annotation algorithm; a localized bipolar voltage assessment; and an algorithm for automatic regional vector analysis, allowing to determine the directionality of the electrical wavefront and to display a quantitative assessment of LCV 12 —Supporting Information. Of note, localized bipolar voltage assessment allows automatic and dynamic adjustment of the window of interest focusing on the near‐field signal and excluding any far‐field component from the measurement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anter et al 7 have reported a different method, whereby multicomponent electrograms (EGMs) were annotated according to their spatiotemporal properties. Recently, Cortez‐Dias et al 8 have reported a novel “late potential map” (LPM) algorithm, which both automatically detects local abnormal ventricular activity (LAVA) and displays local conduction velocity (LCV). Whilst this is not currently available for independent assessment, it promises to be part of future versions of the CARTO 3 mapping system (Biosense Webster Inc.).…”
mentioning
confidence: 99%
“…In this issue of The Journal, Lima da Silva et al 8 performed retrospective offline analysis of the VT substrate using this new LPM algorithm (REF). They included 16 patients with longstanding ischaemic cardiomyopathy; 3 were mapped in 3 different wavefronts, 9 in 2 wavefronts, and 4 in only 1 wavefront.…”
mentioning
confidence: 99%